Studi Kritis Terhadap Pandangan Muhammad Al-Ghazali Tentang Hadis Âhâd dalam Kitab As-Sunnah Al-Nabawiyyah Baina Ahl Al-Fiqh Wa Ahl al-Hadits - Ardiansyah Ardiansyah; Heri Firmansyah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
A Critical Study of Muhammad Al-Ghazali's View of the Âhâd Hadith in the Book of As-Sunnah Al-Nabawiyyah Baina Ahl Al-Fiqh Wa Ahl al-HaditsOne of the leading contemporary muhaddist scholars who came from Egypt is Sheikh Muhammad Al-Ghazali. Among his monumental works in the study of hadith is a book of hadith criticism entitled "as-Sunnah al-Nabawiyyah baina Ahl al-Fiqh wa Ahl al-Hadîts". This article seeks to explain how Sheikh al-Ghazali's views in providing a method for understanding authentic hadiths and the position of ahad hadith as the basis of Islamic law as well as some of his criticisms of the weaknesses of the observations of some ahad hadith even though in some assessments of classical scholars it falls into the category of sahih hadith. The method used in this paper is content analysis, which examines the thoughts of Sheikh Muhammad al-Ghazali on the book he wrote regarding the hadith of ahad, with an empirical rationality approach The ahad hadith that are used as examples in Shaykh al-Ghazali's criticism in this paper are the hadith about flies and the hadith about the prohibition of songs and music. For Sheikh Al-Ghazali, it is not a problem for someone not to practice the hadith Ahad, even if it is authentic (shahih), as long as the hadith is not about faith and the pillars of Islam, such as not practicing the hadith about flies and musics, because this will not damage and disturb one's faith and Islam.